THE EFFECT OF NURSING ETHICAL TRAINING ONTHE REINFORCEMENT OF NURSES’ ROLE IN ETHICAL DECISION MAKING AT PRIVATE HOSPITALS IN MEDAN - ali sabela hasibuan; Jenny Marlindawani Purba (International Journal of Nursing and Health Services (IJNHS), 2019)
The advancement of nursing sciences and technologies has brought impacts to nurses in providing nursing interventions. It is common for nurses to face ethical dilemma and to make ethical decisions in order to overcome challenges in nursing intervention provision. Nurses are required to have adequate knowledge and competencies in taking ethical decision. This study aims to identify the effect of nursing ethical training on the reinforcement of nurses’ role in ethical decision making. This study was a quasi-experimental research using non-equivalent control group design. The study was conducted at private hospitals in Medan City. The research samples involved 100 respondents who were divided into 2 groups, namely control group (n=50) and intervention group (n=50). The research instrument consisted of a set of questionnaire assessing the demographic data, knowledge, attitude, nurses’ action, and observation. Mann-Whitney U test was performed in data analysis. The results show that nursing ethical training has an effect on the reinforcement of nurses’ role in ethical decision making, including knowledge, attitude, and nursing intervention (U=-3.40, p<0.01; U=-5.45, p<0.00; and U=-2.07, p<0.03) between the control group and the intervention group. Keywords: nursing ethical training, ethical decision making